World War II in Photographs - Cross, Robin (Bath, UK Parragon Publishing, 2001)
Spectacular photographs of the years 1939-1945 with accompanying text, highlight significant events of this world which engulfed the world.
Include Map and Illustrations.
Keywords: World War (1939-1945) -- Military campaigns -- World War (1914-1918)